Avaliação de rampas de escoamento superficial como pós-tratamento de esgoto sanitário de lagoas de estabilização - Nascimento, José Gilmar da Silva do (2012)
This study aimed to evaluate the use of overland-flow system as a method of wastewater posttreatment. The disposition of wastewater in soil has been considered for a long time as an alternative for effluents treatment and post-treatment. However, much of the population is not receptive to this method either due to ignorance or due to a lack of adequate information on the ways of the effluent reuse that can be possible by this technique. The overland-flow system has simple construction and operation, as well as the crop production obtained with this type of technique. For this work, it was used the grass Tifton 85 (Cynodon sp) because it has great adaptability to conditions of high concentrations of nutrients and moisture, showing up as a viable option for cultivation on overland-flow system. Experiments were conducted at Centro de Reuso, located in the Wastewater Treatment Plant of Aquiraz, Ceará. Three ramps runoff were constructed with different slopes, 2%, 4% and 6% with 30 meters long and 10 meters further on the ramp of 6% inclination. Treated wastewater from maturation ponds was applied in the overland-flow system. The application rates tested were 0,2m3 /m.h, 0,3 m3 /m.h and 0,4 m3 /m.h. It was evaluated the system's ability to remove nutrients, nitrogen and phosphorus as well as organic matter. By the quantitative analysis, it was possible to determine which inclination allowed a greater removal and which flow ratio. For rates of 0,2m3 /m.h and 0,3 m3 /m.h, the ramp with 2% inclination reached 57.65% and 57.11% removal of organic matter respectively. In terms of total nitrogen removal, the ramp with 6% inclination showed higher removal rates reaching 57.5%. The phosphorus removal performance was low reaching a maximum of 33.86% removal. The system also showed significant removals of microalgae, which was measured by chlorophyll-a rates with maximum values of 52.44%. In all of the aspects evaluated, the system improved the quality of the final effluent, showing up as a simple and inexpensive technique compatible with the economic reality of the Brazilian northeast.